Analisis Limbah Tambang Emas Konvensional Di Kecamatan Sekotong Kabupaten Lombok Barat - Lalu Kinayung Purbajati; Anis Syakiratur Rizki; Heri Murtawan; Samsul Bahri; Alfian Pujian Hadi (Yayasan Tajuk Indonesia, 2024)
Gold mining in Sekotong District has raised concerns among the government. This gold mining should not be allowed to continue continuously, because it can disrupt the continuity of the ecosystem. One of the main problems is the disposal of mining waste which has damaged the environment. This article was written using the library research method, namely by codifying scientific sources from various journals and articles with the same data and then combining them to obtain information about the impact of gold mining waste in the Sekotong area, West Lombok, West Nusa Tenggara. The wide distribution of mercury and cyanide is due to the fact that these two chemicals are very efficient in processing gold ore. However, both of them are also chemicals that are very dangerous for the environment. In addition, the distribution of heavy metals resulting from waste from traditional gold mining is greatly influenced by soil conditions, such as temperature and rock disintegration. Various biological and microbiological processes can concentrate metals in the soil, and heavy metal contamination usually accumulates at depths of up to 75 cm above the soil surface. Mercury and manganese waste resulting from gold processing can enter river ecosystems, dissolve in the water, and sink to the bottom of the water, where they will accumulate in sediment. This waste not only settles in sediment, but some of it will also enter the body tissues of biota that live in river waters.